Kidney Involvement in SARS-CoV-2 Infection: Peritoneal Dialysis as the Preferred Modality - Marko Baralić; Nikola Stojanović; Selena Gajić; Aleksandar Sič; Aarish Manzar; Ana Bontić; Jelena Pavlović; Mateja N. Bojić; Aleksandra Kezić (Vaccines)
Patients undergoing peritoneal dialysis (PD) represent a uniquely vulnerable population due to intrinsic immunological dysfunction and a high prevalence of comorbid conditions. This review examines the complex interplay between natural and vaccine-induced immune responses to SARS-CoV-2 in this group, focusing on viral entry, immune activation, and immune evasion mechanisms. Particular attention is given to the impaired cellular and humoral responses seen in PD patients, including reduced T-cell function, diminished antibody production, and abnormal cytokine signaling, all of which contribute to an elevated risk of severe COVID-19 outcomes. The immunogenicity and clinical efficacy of various vaccine platforms, including inactivated, vector-based, and mRNA formulations, are critically assessed, with an emphasis on the role of booster doses in enhancing protection amid waning immunity and evolving viral variants. Furthermore, the review highlights the advantages of PD as a home-based modality that is compatible with telemedicine and may reduce the risk of viral exposure. These insights underscore the importance of developing individualized vaccination strategies, maintaining close immunological surveillance, and implementing innovative dialysis care approaches to improve clinical outcomes during the ongoing pandemic and future public health crises. Tailored booster strategies and telemedicine-integrated care models are essential for improving outcomes in this high-risk population.